A Critical Review of China’s Foreign Language Program Development: The Perspective of Language Needs - Tongxi, Gong; Yi, Guo (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Recent years (2014–2017) have seen an explosive growth in foreign language undergraduate programs in Chinese universities, apparently in response to China’s development needs. However, without a precise analysis of China’s foreign language needs, it is impossible to evaluate whether the recent developments in foreign language education will be able to meet the nation’s development needs. This article addresses this issue by calculating China’s foreign language needs through a holistic assessment with 14 indicators. The calculation, mainly based on the practical use of foreign languages and China’s international exchange requirements, identifies the top 10 foreign languages urgently needed by the country and demonstrates the different functions of these foreign languages. In light of China’s national foreign language needs, this article ends with a critical review of foreign language program development in recent years.